The Relationship between Mothers’ Knowledge and Feeding Rules Behavior in Toddlers Aged 6–24 Months - Siska Amelia Sari; Sellia Juwita; Wiwi Sartika (LPPM Universitas Abdurrab, 2025)
Background: Proper eating patterns are very important to meet children’s nutritional needs, which are greater compared to adults. In this regard, at least 1 to 2% of children experience serious eating problems that persist over a long period. Based on WHO data in 2024, 150.2 million children under 5 years old were too short for their age (stunting), 42.8 million were too thin for their height (wasting), and 35.5 million were overweight for their height. According to the Indonesian Nutritional Status Study (SSGI) National Level 2021, Pekanbaru City had a stunting prevalence of 11.4%.Objective: To determine the relationship between mothers’ knowledge and feeding rules behavior in toddlers aged 6–24 months.Methods: This study employed a quantitative approach with a correlational analytic design using a cross-sectional method. The instruments used were a knowledge questionnaire and a behavior questionnaire. The sample consisted of 46 respondents.Results: The study found a ρ-value = 0.003 < α 0.05, indicating a significant relationship between mothers’ knowledge and feeding rules behavior in toddlers aged 6–24 months in the Rejosari Public Health Center working area.Conclusion: The majority of respondents had sufficient knowledge, with 17 respondents (34.8%), and the majority demonstrated sufficient feeding rules behavior, with 20 respondents (43.5%).